The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3an00684k
|View full text |Cite
|
Sign up to set email alerts
|

Towards non-invasive monitoring of non-melanoma skin cancer using spatially offset Raman spectroscopy

Abstract: BCC (Basal cell carcinoma) and SCC (Squamous cell carcinoma) account for the vast majority of cases of non-melanoma skin cancer (NMSC). The gold standard for the diagnosis remains biopsy, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Specifically coupling SRS with bioorthogonal Raman reporters has shown immense potential in biomedical imaging due to high sensitivity and molecular specificity. In depth Raman modalities such as spatially-offset and transmission Raman spectroscopy, 156–160 merged with surface-enhancement Raman spectroscopy (surface-enhancement spatially offset Raman spectroscopy-SESORS), have yet to be combined with bioorthogonal cell – silent Raman tags. We believe that such an approach would entail great potential given the recent advances in the field of theranostics.…”
Section: Discussion-prospects and Potentialmentioning
confidence: 99%
“…Specifically coupling SRS with bioorthogonal Raman reporters has shown immense potential in biomedical imaging due to high sensitivity and molecular specificity. In depth Raman modalities such as spatially-offset and transmission Raman spectroscopy, 156–160 merged with surface-enhancement Raman spectroscopy (surface-enhancement spatially offset Raman spectroscopy-SESORS), have yet to be combined with bioorthogonal cell – silent Raman tags. We believe that such an approach would entail great potential given the recent advances in the field of theranostics.…”
Section: Discussion-prospects and Potentialmentioning
confidence: 99%
“…The BCC spectra show a stronger presence of the 1743 cm −1 band. This may be explained by the lipid contribution from the ester groups in the glycerol heads of triacylglycerol in the adipose tissue below the dermis in the C-O stretching mode [49,60], or it could also suggest a higher amount of melanin owing to more pigment in the BCC patient group, as a subgroup of pigmented BCCs exists [57]. The results indicated a favorable relationship between lipid content and BCC and between protein content and SCC.…”
Section: Clinical Studiesmentioning
confidence: 92%
“…The spectrum data and the related histopathology data were analyzed in order to find potential predictors for lesion detection. PCA revealed that while wavenumbers 507, 631, 772, 870, 1076, 1189, 1268, 1300, 1435, and 1531 cm −1 were linked to SCC, wavenumbers 937, 1003, 1125, 1339, and 1640 cm −1 were not [49]. Certain spectral characteristics distinguishing the two subtypes are bands associated with phenylalanine (at 1003 and 1339 cm −1 ), skeletal (at 937 cm −1 ), and amide I (at 1640 cm −1 ) collagen vibrations, which are notably more pronounced in the SCC type [27,56,57].…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first attempts to incorporate SORS into biomedical research began in 2006, when SORS spectra of bone were obtained, contributing to the development of in vivo bone disease detection in mice and humans. , Further studies have focused on monitoring bone mineralization in tissue engineering and bone healing in rat calvarial defects . However, most importantly, SORS-based techniques have been used to characterize soft tissues, identifying microcalcifications in breast tissue phantoms, nonmelanoma cancer subtypes in skin biopsy samples, and skin changes caused by sunburn studied on human volunteers, thus having introduced entirely novel possibilities for a diverse array of analytical applications. Moreover, integrating SORS with surface-enhanced Raman spectroscopy (SESORS) enables signal detection at greater depths , to reveal and target disease states by sensing glucose concentrations, , neurochemicals, or the presence of tumor spheroids .…”
mentioning
confidence: 99%